2023
DOI: 10.3390/brainsci13050840
|View full text |Cite
|
Sign up to set email alerts
|

Early Hemorrhagic Transformation after Reperfusion Therapy in Patients with Acute Ischemic Stroke: Analysis of Risk Factors and Predictors

Abstract: Background: The standard reperfusion therapy for acute ischemic stroke (AIS) is considered to be thrombolysis, but its application is limited by the high risk of hemorrhagic transformation (HT). This study aimed to analyze risk factors and predictors of early HT after reperfusion therapy (intravenous thrombolysis or mechanical thrombectomy). Material and methods: Patients with acute ischemic stroke who developed HT in the first 24 h after receiving rtPA thrombolysis or performing mechanical thrombectomy were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Lastly, our study revealed insignificant associations between the presenting NIHSS, NCCT-based ASPECTS, and CTP-derived infarct core volume with an increased risk of delayed PH following thrombectomy, which is in contrast with previous literature [ 3 , 27 ]. Nonetheless, our analysis identified a trend toward an increased risk of delayed PH in patients with higher presenting NIHSS, lower NCCT-based ASPECTS, and larger CTP-derived infarct core volumes, although statistical significance was not attained within our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Lastly, our study revealed insignificant associations between the presenting NIHSS, NCCT-based ASPECTS, and CTP-derived infarct core volume with an increased risk of delayed PH following thrombectomy, which is in contrast with previous literature [ 3 , 27 ]. Nonetheless, our analysis identified a trend toward an increased risk of delayed PH in patients with higher presenting NIHSS, lower NCCT-based ASPECTS, and larger CTP-derived infarct core volumes, although statistical significance was not attained within our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Another interesting study found a correlation between an increased NIHSS score and the concomitant presence of atrial fibrillation and tumors [85]. These data regarding the concomitant presence of atrial fibrillation have not been confirmed in other studies [81], while, with regard to the diagnosis of a concomitant neoplasm, it is difficult to find case series that evaluate patients also for the purposes of researching a neoplasm occult. To conclude, a review demonstrated that the occurrence of hemorrhage in the context of an ischemic area depends on many factors, including the location and size of the infarct and poor collateral vascularization, confirming what has been said previously [86].…”
Section: Size and Severity Of The Hemorrhage And Ischemic Stroke Riskmentioning
confidence: 90%
“…In the case of a cardioembolic stroke, the numerousness of the clots was predictive of the overlap of a hemorrhagic complication considering the possibility that, in this case, there could be a greater extension and a multiplicity of the infarcted brain areas [72,80]. Iancu et al [81] looked for risk factors and hemorrhagic transformation in patients with an initial diagnosis of ischemic stroke. Among these, the presence of male sex, high glycemic values of arterial hypertension at baseline, and high values of NIHSS and ASPECTS scores were all associated with a significantly elevated risk of hemorrhagic transformation [81].…”
Section: Size and Severity Of The Hemorrhage And Ischemic Stroke Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms persist for a duration exceeding 24 h or may even culminate in the patient's death. Notably, the only discernible causative factor for these symptoms should be of vascular origin, unless there are specific interventions like surgery or medication that might interrupt this course" [176]. This clearcut definition, along with the combined insights from imaging and clinical examinations, solidifies the diagnostic accuracy, ensuring patients receive the most appropriate and timely care.…”
Section: Comprehensive Cerebral Imaging: Collaborative Diagnostics In...mentioning
confidence: 99%